Reviewing congruity effects in the service environment musicscape - Oakes, S.; North, Adrian (Emerald Group Publishing Ltd., 2008)
Purpose – The purpose of this paper is to present a literature review that highlights significant findings from empirical research examining the impact of music within various real and simulated service environments. Design/methodology/approach – The paper examines the results of studies that have manipulated specific musical variables (genre, tempo, volume, and liking), and attempts to identify consistent patterns of findings to guide managers and researchers. The studies focus upon a range of dependent variables including evaluation of the environment, perceived wait and stay duration, consumption speed, affective response, and spending. Possible explanations for apparently inconsistent findings are discussed. Findings – A variety of studies reveal the positive influence of musical congruity upon desired outcomes. Future research proposals identify the need to examine defining-attribute and prototype theories of musical congruity. Originality/value – The review highlights a range of implications drawn from the studies that will be of value to service organization managers who use music as a key component of their servicescape in order to enhance desired cognitive and affective responses.